Longitudinal analysis of need-service matching for substance-involved parents in the child welfare system. (July 2020) - Lin, Yu-An; Hedeker, Donald; Ryan, Joseph P.; Marsh, Jeanne C.
Highlights: Substance-using parents in the child welfare system require matched services. Integrated services may not help substance-using parents reunify with children. Assertive case management for substance-using parents reduces the need-service gap. Recovery coaches help substance-using parents get matched services. Recovery coaches promote family reunification. Abstract: Objective: The study documents the impact of the need-service gap (client did not receive the service they need) on family reunification status among substance-involved parents in the child welfare system. Methods: With a sample of 271 substance-involved parents involved with the Illinois foster care system, we used a longitudinal Poisson model to identify the group by time effect on the expected need-service gap between reunified and not-reunified parents. Results: Two major findings emerge: (1) when working with recovery coaches, the trend of substance-involved parents' need-service gap declined over time, and (2) the expected rate of the need-service gap was not significantly different between reunified and not-reunified parents in the early stage of intervention. However, after accounting for the group by time effect, starting from the second assessment period, the expected need-service gap was significantly less for reunified parents than for not-reunified parents. Conclusions: This longitudinal analysis reveals that an assertive case management child welfare intervention for substance-involved parents can reduce the need-service gap. Substance-involved parents who reunified with their children are likely to have fewer unmatched needs across the intervention. This study provides evidence that matching services to needs is associated with family reunification.